ANALISIS KEBIJAKAN KINERJA SATUAN POLISI PAMONG PRAJA KABUPATEN TULANG BAWANG DI MASA PANDEMI COVID-19 - ida farida; Muhammad Thoru (Universitas Bandar Lampung (UBL), 2021)
The problems in this paper are (1) How is the performance policy of the Tulang Bawang Regency Civil Service Police Unit during the Covid-19 Pandemic? (2) What are the aspects that hinder the performance of the Tulang Bawang Regency Civil Service Police Unit during the Covid-19 Pandemic? The type of research used in this study is a qualitative research method approach. The process of qualitative data analysis is carried out with the stages of data reduction, data presentation (display) and drawing conclusions (verification). Based on the results of the study, it can be concluded that the performance policy of the Tulang Bawang Regency Civil Service Police Unit during the Covid-19 Pandemic was seen from the five variables presented by Robbins, namely aspects of quality, quantity aspects, punctuality aspects, effectiveness aspects and independence aspects. Aspects that hindered the implementation of the performance of the Tulang Bawang District Civil Service Police Unit during the Covid-19 Pandemic include organizational structure, human resources, operational funds, facilities owned, lack of human resources for employees in the field of science and technology and limited funding allocated for implementation of main tasks and functions